The American Negro and Marxist- Leninist Self- Determination: The History, Development, and Application of the Theory of Self- Determination for African- Americans by the Communist Party of the United States 1928-1959. - LeMere, Jess (My University, 2010)
This paper historically traces the Communist program of self-determination for African-Americans pointing out key facets of the program as well as important developments and turning points along the way. It begins with an exploration of the origins of the program with a look at Vladimir Lenin and Joseph Stalin during the Bolshevik Party's rise to power in Russia. It follows the development of the theory under Harry Haywood at the Lenin School in Moscow. It traces the Communist International in its adoption of the 1928 and 1930 Resolutions of the Black National Question. The paper finishes by tracing the history of the program as it falls in and out of favor within the highly factional Communist Party of the United States of America.
Keywords: African Americans--History--1877-1964; Communism and civil rights--United States--History; Communist Part of the United States of American--African American membership; Communism--United States--History--20th century; Socialism--United States--History--20th century